2017
DOI: 10.1093/jnci/djw306
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Sequencing and Patient-Derived Xenografts in the Neoadjuvant Treatment of Breast Cancer

Abstract: Background: Breast cancer patients with residual disease after neoadjuvant chemotherapy (NAC) have increased recurrence risk. Molecular characterization, knowledge of NAC response, and simultaneous generation of patient-derived xenografts (PDXs) may accelerate drug development. However, the feasibility of this approach is unknown.Methods: We conducted a prospective study of 140 breast cancer patients treated with NAC and performed tumor and germline sequencing and generated patient-derived xenografts (PDXs) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 26 publications
2
87
1
2
Order By: Relevance
“…This is consistent with other studies that have previously shown lower pCR rates in HR-positive disease. [7, 13, 37] Additionally, the number of breast cancer recurrences or deaths in the patients who achieved a pCR was so small that statistical comparison of the impact of pCR on outcome was limited. Since these patients are treated with adjuvant endocrine therapy for 5 years and in some instances 10 years after surgery, they remain at risk for future breast cancer events for over 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies that have previously shown lower pCR rates in HR-positive disease. [7, 13, 37] Additionally, the number of breast cancer recurrences or deaths in the patients who achieved a pCR was so small that statistical comparison of the impact of pCR on outcome was limited. Since these patients are treated with adjuvant endocrine therapy for 5 years and in some instances 10 years after surgery, they remain at risk for future breast cancer events for over 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts are therefore being taken to develop collections of heterogeneous patient-based models of TNBC that can be used to contrast therapeutic sensitivities and link antitumor responses to molecular traits that may only be present in subsets of patients (1215). In particular, due to the poor outcomes for TNBC patients who harbor significant residual disease following neoadjuvant NeoCT, models derived from post-NeoCT, residual tumors are of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate the utility of GeneSet MAPR, we report a detailed analysis of a gene set that is differentially expressed between triple negative breast cancer patients who exhibited pathological complete response (pCR) to a chemotherapy regimen and those who did not (non-pCR) (24). This gene set was derived from a longitudinal study named 'BEAUTY' at the Mayo Clinic and we refer to it as 'BEAUTY TRIPLE NEGATIVE RESPONSE' or 'BTNR' gene set.…”
Section: Mapr Analysis Of Genes Associated With Patient Response To Cmentioning
confidence: 99%
“…While some members of these families were included in the BTNR set, they were not mentioned in the BEAUTY study (24). MAPR's ranking brought them to attention.…”
Section: Mapr Analysis Of Genes Associated With Patient Response To Cmentioning
confidence: 99%
See 1 more Smart Citation